Data Management of Talent Management Information System for Promotion and Mutation of Constitutional Court Employees Based on Website - Widy Hastowahyudi; Atit Pertiwi (Green Publisher Indonesia, 2025)
This research highlights the importance of implementing ASN Talent Management in accordance with Article 8 paragraph (2) of PANRB Ministerial Regulation Number 3 of 2020, which requires government agencies to implement talent management based on needs analysis to support the achievement of the vision, mission, and priorities of national development. This system is designed to implement a Merit System that supports succession patterns and career development in a transparent and accountable manner. By utilizing information technology, the talent management system becomes more efficient, accountable, and easily accessible, helping to compare employee qualifications, competencies, and performance with position requirements. The research uses Research and Development (R&D) methodology with waterfall method and Unified Modeling Language (UML) modeling to produce design diagrams, such as Use Case, Activity, Sequence, and Class Diagram. System validation is done through User Acceptance Testing (UAT) with a Likert scale to assess aspects of design, usability, efficiency, and reliability. The test results show an average score of 81.67%, which is classified as very good, indicating the system meets the needs of information-based performance appraisal with accurate results and supports the implementation of talent management as a whole.